2021
DOI: 10.30564/jesr.v4i1.2716
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth, Industrialization, Trade, Electricity Production and Carbon Dioxide Emissions: Evidence from Ghana

Abstract: The study scrutinized correlation between electricity production, trade, economic growth, industrialization and carbon dioxide emissions in Ghana. Our study disaggregated trade into export and import to spell out distinctive and individual variable contribution to emissions in Ghana. In an attempt to investigate, the study used time-series data set of World Development Indicators from 1971 to 2014. By means of Autoregressive Distributed Lag (ARDL) cointegrating technique, study established that variables are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In the given models, CO 2 , Y, IO, and UR represent carbon dioxide emissions, total output, industrial output, and urbanization, representing I, A, T, and P in the STIRPAT model, respectively. The variables CO 2 , Y, IO, and UR employed for I, A, T, and P are similar to earlier studies Al-Mulali, U. et al (2015) [11], Saidi and Mbareak (2017) [24], and Appiah et al ( 2019) [50]. In terms of additional variables, FD stands for financial development, TO stands for trade openness, NRE stands for non-renewable energy, and RE stands for renewable energy.…”
Section: Theoretical Framework Of the Modelsupporting
confidence: 54%
See 1 more Smart Citation
“…In the given models, CO 2 , Y, IO, and UR represent carbon dioxide emissions, total output, industrial output, and urbanization, representing I, A, T, and P in the STIRPAT model, respectively. The variables CO 2 , Y, IO, and UR employed for I, A, T, and P are similar to earlier studies Al-Mulali, U. et al (2015) [11], Saidi and Mbareak (2017) [24], and Appiah et al ( 2019) [50]. In terms of additional variables, FD stands for financial development, TO stands for trade openness, NRE stands for non-renewable energy, and RE stands for renewable energy.…”
Section: Theoretical Framework Of the Modelsupporting
confidence: 54%
“…Zhao et al [49] used the Log Mean Divisia Index and concluded that the major factor behind high carbon emissions was industrial output in Shanghai. Appiah et al [50] identified a causal link between industrialization and CO 2 emissions.…”
Section: Industrialization-pollution Nexusmentioning
confidence: 99%
“…Studies have shown a two-way relationship between CO 2 emissions and industrialization [29] [30]. Studies also reconfirmed the Environmental Kuznets Curve between industrial development and CO 2 emissions in both short and long term, in addition, CO 2 emissions are also affected by population density and trade [31] [32] [33] [34]. They also showed that the economy is moving toward the use of clean, renewable energy [33] [35].…”
Section: Introductionmentioning
confidence: 96%